Seaways to Complexity. - Anne Lene Melheim (Viking, 2022)
Bokanmeldelse av boka Seaways to Complexity. A Study of Sociopolitical Organisation Along the Coast of Northwestern Scandinavia in the Late Neolithic and Early Bronze Age, Equinox, 2021. Av Knut Ivar Austvoll.